Avaliação do potencial antinociceptivo e anti-inflamatório do 2-[(3,5-di-tert-butil-4-hidroxifenil)metileno]hidrazinacarboximidamida (LQM10), um derivado de guanilhidrazona - Silva, João Paulo Noé da (2019)
The inflammatory response is described as an organism reaction that aims purpose is to contain/eliminate aggressive agents and promote tissue repair. However, when inflammation goes beyond the physiological limits, pathogenesis is established for several types of diseases. The synthesis and characterization of new drugs, capable of inhibiting inflammation, are still essential as currently available therapies that have significant limitations and adverse effects. Guanylhydrazones are shown as a group of important molecules for different fields of study including the biomedical and medicinal chemistry areas. Once the structural modifications already made in guanylhydrazones have allowed the obtaining of a large number of new molecules possessing a wide range of pharmacological effects, including antioxidant and antiviral activities. Based on the relevance of guanylhydrazone derivatives, as well as the absence of pharmacological evaluations of their possible analgesic and anti-inflammatory effects. In this study, the goal was to evaluate the antinociceptive and anti-inflammatory effects of the guanylhydrazone derivative called 2 - [(3, 5-di-tert-butyl-4-hydroxyphenyl) methylene] hydrazinecarboximidamide, also known as LQM10. Initially, nociceptive response induced by intraperitoneal (i.p.) injection of acetic acid was significantly inhibited by the treatment with LQM10 from the concentration of 0.0305 μmol / kg. Next, in this same experimental model, the use of the antagonists: yohimbine, atropine, and glibenclamide were not able to reverse the antinociception induced by LQM10. In the formalin test, treatment with LQM10 at the highest doses of 15.25 and 30.5 μmol / kg inhibited the response, respectively, by 50 and 53% only in the second phase of this test. Treatment with LQM10 also did not affect the nociceptive response induced by the hot plate model. In nociception induced by capsaicin, treatment with 3.05, 15.25 and 30.5 μmol / kg of LQM10 decreased the nociceptive response by 38%, 46%, and 43%, respectively. Additionally, animals treated with LQM10 showed no motor performance alterations when evaluated in the rota-rod test. When assessing the effect of this guanylhydrazone derivative on the formation of inflammatory edema, it was found that the treatment with LQM10 significantly inhibited the formation of carrageenan-induced paw edema. Additionally, in the in vitro system, using A549 cell culture, we found that cells exposed to LQM10 for 24 h at concentrations below 10 μM did not have their viability affected. When A549 cells were stimulated with TNF-α, there was an increase in the production of the reactive species of oxygen, nitric oxide, and IL-6, phenomena that were inhibited by the treatment with LQM10. Together, these results demonstrate that LQM10 has an antinociceptive effect that seems to depend on vanilloid receptors. In addition, has an anti-inflammatory effect capable of inhibiting the generation of pro-inflammatory mediators as reactive species of oxygen, nitric oxide, and IL-6 cytokine.